Stress Management Mechanisms in Younger Athletes - Korobeynikov, Georgiy; Korobeinikova, Lesia; Korobeinikova, Ivanna; Kokhanevich, Anatoliy (International Journal of Pediatrics and Child Health, 2023)
Background/Purpose: Physiological responses to stress are associated with tension in the autonomic nervous system. One of the physiological reactions to stress is the tension of the autonomic nervous system. Intense physical activity and emotional stress can provoke mental stress in young athletes. Purpose - to study the features of the mechanisms of stress management in young athletes. Method: Method: 30 younger athletes were examined (Greco-Roman wrestlers, 13-16 years old). Young athletes represented the Kremenchug sports club. Heart rate variability (HRV) was assessed using a Fazagraph computer electrocardiograph (Ukraine). The characteristics of the statistical and frequency analysis of heart rate were evaluated. HRV indicators were recorded before and after the competition. The study of statistically significant difference between the obtained results carry out with help Wilcoxon rank sum test. Results: During the competition the meaning of LF increases with simultaneous a decrease in HF oscillation. This fact is associated with a high level of tension in the regulatory mechanisms of HRV in younger athletes in a competitive state. At the same time, the parasympathetic activity of autonomic regulation is decline. Result shows the development of stress during psycho-emotional strain in competition condition. The stress caused by competitive situation in younger athletes is characterized by an increase in the tension of the autonomic regulation of HRV with deterioration in sympathetic and parasympathetic activity. The stress caused by competitive situation in younger athletes is characterized by an increase in the tension of the autonomic regulation of HRV with deterioration in sympathetic and parasympathetic activity. Conclusion: It was revealed that the conditions of competition among young athletes provoke a stress reaction with a predominance of sympathetic regulation. The mechanism of prevention of competitive stress in younger athletes is associated with a change in the ratio of autonomic regulation of the heart rate.